2022
DOI: 10.21608/jpps.2022.284077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Spacing and N Fertilization Levels of Watermelon Relay Intercropping with Faba Bean in Relation to Yield Productivity

Abstract: This study suggested growing faba beans in the watermelon cultivated area by relay intercropped melon with faba bean to reduce the faba bean production-consumption gap, maximize the productivity per unit area, reduce the use of nitrogen fertilizer and increase the income of farms. So, A field experiment was implemented during 2020/2021 and 2021/2022 seasons at Ismailia Experiment Station, ARC, Ismailia Governorate, Egypt, to study the effect of plant spacing (50, 75 and 100 cm) and N fertilization levels (40, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Present findings are in conformity with the results reported by [8 and 9] in hybrid cucumber; [10] in watermelon.…”
Section: Fruits Per Plantsupporting
confidence: 94%
“…Present findings are in conformity with the results reported by [8 and 9] in hybrid cucumber; [10] in watermelon.…”
Section: Fruits Per Plantsupporting
confidence: 94%
“…It can be inferred from the table that spacing, fruit thinning and nutrient management had significant effect on the number of vines produced by plants. Spacing level D 1 recorded the maximum (6.45) vines per plant and the minimum (5.28) vines per plant were produced by plants in spacing level D 3 (1.00 m x 1.00 m).The present finding is in consonance with the reports of Adlan and Sarra (2018) [24] and Allah et al (2022) [12] in watermelon. The competition for nutrient, space and light is less in wider spacing as compared to the narrower spacing which helps in better incorporation of light and more photosynthesis.…”
Section: Number Of Primary Vinessupporting
confidence: 92%
“…2.5 m x 2.0 m recorded the highest vine length of 326.28 cm. Dantata (2014) [11] and Allah et al (2022) [12] also reported similar findings in watermelon. The significant increase of vine length with increasing spacing may be due to the fact that the competition for nutrient, space, water and light was less in wider spacing as compared to the narrower spacing.…”
Section: Resultsmentioning
confidence: 58%